A Phenolic ester from aglaia loheri blanco leaves is a potential anticancer agent - Dapat, Else G. (2011)
Leaves of Aglaia loheri from the plant family Meliaceae were screened for cytotoxicity using HCT 116, human colon carcinoma cell line. The crude extract was fractionated and yielded an active isolate, Maldi 531.2[M+H]+ which was investigated for its in vitro cytotoxicity against human leukemia cells, CCRF-CEM and their multi-drug resistant (MDR) type, ADR5000-CEM. Changes in the intrinsic mitochondrial membrane potential (Δψm) on MDR leukemic cells was also evaluated and analyzed for apoptosis after treatment with the active isolate. Its possible effect to topoisomerase enzyme was also investigated. Its specificity to P-gp was also determined as well as its effects on MDR activity in combination with another substrate, verapamil. Maldi 531.2[M+H]+, a phenolic ester showed potent anti-cancer activity against both CCRF-CEM and ADR5000-CEM cells with an IC50 of 0.02 and 0.03 μM, respectively. The active isolate further caused a significant reduction of the Δψm of MDR cells in a dose-dependent manner, suggesting apoptosis as monitored by Annexin V-FITC/ PI staining. Maldi 531.2[M+H]+ is a substrate of P-gp that can enhance MDR activity at low concentration by cooperative stimulation with low concentration of verapamil; and can inhibit MDR activity at higher concentration by competitive inhibition with higher concentration of verapamil. Thus, Maldi 531.2[M+H]+ may be a potential anti-cancer agent. These results could contribute to studies being done for the improvement of current chemotherapy options that can pave a way to combination therapy for cancer cells which are resistant to one drug but remain susceptible to other drugs.
Vita.
"October 2011."
Thesis (Ph.D. Biology)--University of the Philippines Diliman.
Keywords: Antineoplastic agents; Phenols